Contribution Of Limb Length And Brick Flexibility to Smash Ability In Volley Balls Lueng IE Aceh Big White Elang - Syamsulrizal, Syamsulrizal; Iqbal, Muhammad; Zahara, Zahara (INSPIREE: Indonesian Sport Innovation Review, 2023)
The  purpose  of  the study. This study aims to study and find out this method is used to obtain information directly from informants regarding "The Contribution of Leg Length and Flexibility of Togok To The Ability Of Volleyball Smash At The White Eagle Club Lueng Ie Aceh Besar 2021. Materials and methods. as for the data collection technique using tests and measurements with 15 athletes (Jimenez et al., 2016). The samples available in this study were 12 athletes due to sampling where the number of samples was the same as the population. Using the total sampling technique because according to (Hendra, n.d.) the total population is less than 100 and the entire population is used as a research sample. Results. the results of the calculation of t count smaller than t table or -3.83<2.178813 . This means that the description shows that the hypothesis that the author formulated is that there is no jointly significant contribution between leg length and togok flexibility on the volleyball smash ability of the Lueng ie 2021 white eagle club athlete Conclusions. There is no significant contribution between leg length and togok flexibility with volleyball smash ability in volleyball athletes at the white eagle club Lueng ie. Aceh Besar 2021.